2018
DOI: 10.1055/a-0633-2814
|View full text |Cite
|
Sign up to set email alerts
|

High Serum Fractalkine is Associated with Lower Trabecular Bone Score in Premenopausal Women with Graves’ Disease

Abstract: Chemokine CX3CL1 (fractalkine) may be an important factor linking thyroid status and bone remodeling, through tetrac, a derivative of thyroxine. This study explores the relationship between serum fractalkine levels and parameters of thyroid status and bone in premenopausal women with Graves' disease (GD) in comparison to healthy controls. This cross-sectional study included three premenopausal female groups: active GD; cured GD, and healthy age-, gender-, and BMI-matched controls. Measurement of serum fractalk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 25 publications
1
10
0
2
Order By: Relevance
“…No association was shown between lumbar BMD and thyroid hormones levels, whereas high-normal FT4 levels were negatively correlated with TBS in postmenopausal women (44). Very recently, Kuzma et al showed a lower TBS value in 21 premenopausal women with untreated Graves' disease compared to healthy controls (45). Among patients given TSH suppressive therapy, different studies showed an impairment of TBS especially in postmenopausal women.…”
Section: Trabecular Bone Score (Tbs) and Quantitative Computed Tomogrmentioning
confidence: 98%
“…No association was shown between lumbar BMD and thyroid hormones levels, whereas high-normal FT4 levels were negatively correlated with TBS in postmenopausal women (44). Very recently, Kuzma et al showed a lower TBS value in 21 premenopausal women with untreated Graves' disease compared to healthy controls (45). Among patients given TSH suppressive therapy, different studies showed an impairment of TBS especially in postmenopausal women.…”
Section: Trabecular Bone Score (Tbs) and Quantitative Computed Tomogrmentioning
confidence: 98%
“…Other studies based on a group of premenopausal women showed that Graves' Disease is in strong correlation with decreased TBS, whereas the BMD still did not differ between active the Graves' Disease group and the control group [55].…”
Section: Thyroid Diseasesmentioning
confidence: 75%
“…In a cross-sectional controlled study of premenopausal women with Graves' disease, Kuzma et al found that TBS [32].…”
Section: Discussionmentioning
confidence: 99%